Intercultural Communicative Competence in the virtual education - Mardonov , Abdullo (The Lingua Spectrum, 2025)
This article explores the development of Intercultural Communicative Competence (ICC) within virtual learning environments. It highlights the increasing importance of ICC in today’s interconnected world and examines key theoretical frameworks that underpin its understanding. The text emphasizes the crucial role of language, not merely as a tool for communication, but as an embedded element of cultural contexts. It discusses the impact of technology, acknowledging both the challenges and opportunities presented by digital communication, including the influence of social media algorithms. The article underscores the need for a multifaceted approach to cultivating ICC in virtual learning environments, emphasizing the importance of authentic experiences, critical thinking, and ethical considerations such as digital citizenship. Ultimately, the article aims to empower learners to become effective intercultural communicators in the digital age.